2017
DOI: 10.1016/j.actaastro.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a Rotating Detonation with a realistic injector designed for separate supply of gaseous hydrogen and oxygen

Abstract: To cite this version:Thomas Gaillard, Dmitry Davidenko, Francis Dupoirieux. Numerical simulation of a rotating detonation with a realistic injector designed for separate supply of gaseous hydrogen and oxygen. 2017. Numerical simulation of a rotating detonation with a realistic injector designed for separate supply of gaseous hydrogen and oxygen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…3e indicates 33% of the injected fuel is consumed at the surface of contact, so only 67% of the reactive mixture is burned by detonation combustion. A similar phenomenon is also observed by Gaillard et al (2017) that 30% of the injected mass is consumed by the contact-surface chemical reaction. Such chemical reactions burn fuel at approximately constant pressure conditions, so they generate more entropy than detonation combustion (Kailasanath, 2000;Heiser and Pratt, 2002), which is unfavorable to improve the thermal cycle efficiency.…”
Section: Flow Field Of Stratified Injectionsupporting
confidence: 79%
See 2 more Smart Citations
“…3e indicates 33% of the injected fuel is consumed at the surface of contact, so only 67% of the reactive mixture is burned by detonation combustion. A similar phenomenon is also observed by Gaillard et al (2017) that 30% of the injected mass is consumed by the contact-surface chemical reaction. Such chemical reactions burn fuel at approximately constant pressure conditions, so they generate more entropy than detonation combustion (Kailasanath, 2000;Heiser and Pratt, 2002), which is unfavorable to improve the thermal cycle efficiency.…”
Section: Flow Field Of Stratified Injectionsupporting
confidence: 79%
“…Due to the unique advantages of detonation combustion, more scholars have begun to pay attention to the use of detonation to achieve aerospace propulsion. In recent years, the use of detonation for energy release in engines As injection remains the key issue affecting RDE's performance, a large number of studies on the effect of injection have been carried out Tsuboi et al, 2015;Gaillard et al, 2017;Smirnov et al, 2018Smirnov et al, , 2019Zhang et al, 2018;Wang et al, 2019;Zheng YS et al, 2019). Smirnov et al (2018Smirnov et al ( , 2019 tested the initiation and propagation process of rotating detonation wave using three types of gas mixture and different injection patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some preliminary 3D simulations were also studied. [18][19][20][21][22][23] Eude et al 24 used the adaptive mesh refinement to calculate the 3D simulations of RDE. They found that the pressures at inner and outer wall were different because of the effect of the curvature, and the effected curvature become larger when the chamber diameter reduced and the chamber width increased.…”
Section: Introductionmentioning
confidence: 99%
“…This reactant fill-zone is where fuel and oxidizer are available for combustion just upstream of each detonation wave. In this way, each successive detonation wave passes through sufficient fuel and oxidizer to sustain it [6]. Above each detonation wave, an oblique shock and shear layer form.…”
Section: Introduction 1rdre Overviewmentioning
confidence: 99%